Le secteur financier et le développement économique du Québec - Ryba, André (L'Actualité économique)

(untitled) (HEC Montréal, 1974)
AbstractThis paper which reflects the methodology and the findings of a larger study present a regional analysis of the Canadian financial sector. It denotes an historical tendency towards overconcentration of financial institutions and activities in Toronto which emerges more and more as the only financial center in Canada. Financial intermediation is weakening in other parts of the country (British Columbia excepted), particularly in Quebec to which this article devotes most of its attention. The study of the interrelation between the financial sector and industrial activity strongly suggests that the absence of an active financial sector in a region, which has reached a stage of development comparable to that of Quebec, constitutes an impediment to a balanced economic development of that region. This result is strengthened when the output of a financial sector is enlarged to two jointly produced goods, capital and information, and when the information and transaction costs involved in the production of those two goods are taken into account. The main conclusion of this paper is that there may be conflicts between the pursuit of the greatest efficiency per se of a financial sector and the pursuit of the greatest efficiency in regard to economic development.